EDUKASI PENTINGNYA MENJAGA KEBUGARAN FISIK UNTUK MENCEGAH SINDROM METABOLIK PADA KARYAWAN UNIVERSITAS KATOLIK INDONESIA ATMA JAYA (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
Productivity and performance quality of an individual are influenced by their physical fitness. However, the National Sport Development Index data for 2021 by the Ministry of Youth and Sports indicates that 76% of the Indonesian population has poor physical fitness, with 53.63% being in the very poor category. Low levels of knowledge, motivation, and the availability of facilities are factors contributing to the poor physical fitness in Indonesia. In addition to being a determining factor in employee productivity and performance quality, poor physical fitness is also a risk factor for psychological stress and various non-communicable diseases, such as type 2 diabetes, obesity, and others. The purpose of this community service activity is to assess the level of understanding among the community, especially employees, regarding the importance of physical fitness for health in preventing metabolic syndrome; and to provide education on the significance of physical fitness for health as an investment in future well-being. The methods used include lectures, video screenings, discussions, and concluded with an evaluation of understanding through pretests and posttests. The results of the pretest and posttest showed a significant improvement of knowledge from 28.59% to 36.34% (p
Keywords: Employees; knowledge; non-communicable diseases; physical fitness